Collector characterisation and heat loss tests on a novel batch solar water heater with CPC reflector for households. Issue 7 (6th June 2020) - Varghese, Jaji; Samsher,; Manjunath, K.
ABSTRACT: This solar water-heating unit is an integration of the older concept of batch water heating with the modern trends in solar water-heating technologies i.e. incorporating a concentrator in the design. The concentrator used is the compound parabolic type (CPC) which is a non-imaging device having wider acceptance angle (64°) and supported on a wooden cradle, which comprises the two arms of the parabola. To suppress the heat loss, an air gap has been introduced in the arms of the CPC. The collector is a single larger diameter drum which serves both as an absorber and storage unit positioned at the focus of CPC. The parametric study of the model showed the thermal efficiency of the collector as high as 38% and maximum water temperature attained was 53°C. Heat loss tests performed on the collector on a 24-hr cycle period showed good long time performance estimates. The response time of collector computed and performance characteristic curve plotted to predict system response under any given conditions of solar insolation and ambient temperature.